2022
DOI: 10.3389/fendo.2022.816606
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Matured Oocytes From Mice of Advanced Reproductive Age Exhibit Alternative Splicing Processes for Mitochondrial Oxidative Phosphorylation

Abstract: The mean age of women seeking infertility treatment has gradually increased over recent years. This has coincided with the emergence of in vitro maturation (IVM), a method used in assisted reproductive technology for patients with special requirements. However, when compared with conventional in vitro fertilization, IVM is associated with poor embryonic development potential and low live birth rates, thus limiting the widespread application of this technique. In this study, we performed RNA-sequencing transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The OXPHOS pathway is a significant source of ATP production in mitochondria and depends on five multisubunit respiratory chain protein complexes that are directly involved in oocyte maturation [ 34 ], fertilization [ 35 ] and preimplantation development of embryos [ 36 , 37 ]. In the current study, we found that the first and fifth complexes of the respiratory chain had the highest number of DEGs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The OXPHOS pathway is a significant source of ATP production in mitochondria and depends on five multisubunit respiratory chain protein complexes that are directly involved in oocyte maturation [ 34 ], fertilization [ 35 ] and preimplantation development of embryos [ 36 , 37 ]. In the current study, we found that the first and fifth complexes of the respiratory chain had the highest number of DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NDUFA3 is located in the inner mitochondrial membrane and communicates with the previously mentioned core subunits ND1, ND3 and NDUFS8 and with the supernumerary subunits NDUFA8 and NDUFA13. Qin et al [ 37 ] reported that the expression of NDUFA3 was downregulated in in vivo matured oocytes compared to in vitro matured oocytes, which are generally considered to have lower developmental competence [ 37 ]. In contrast, in our study, we demonstrated higher expression of NDUFA3 in blastocysts derived from oocytes collected from pubertal heifers than in those derived from prepubertal heifers, which in turn accounts for their better developmental competence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations